Multidisciplinary Approach to Perihilar and Intrahepatic Cholangiocarcinoma: A Single-Center Experience - Gundogdu, Adnan; Kodalak, Taha Anil; Kucukaslan, Hakan; Topaloglu, Serdar; Turali, Ummuhan; Oguz, Sukru; Dohman, Davut; Dinc, Hasan; Ozdemir, Feyyaz; Arslan, Mehmet; Cobanoglu, Umit; Karabulut, Erdem; et al. (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Treatment of perihilar cholangiocarcinoma (PHCC) and intrahepatic cholangiocarcinoma (IHCC) is a challenging issue. We aimed to investigate the clinical characteristics of both tumors and the outcome of our treatment policy. Material and Methods: We retrospectively analyzed data of 117 patients who were diagnosed with PHCC or IHCC between January 2007 and September 2023. Postoperative outcomes and the effects of prognostic factors on overall survival (OS) were investigated. Results: Surgical resection was performed on 47 patients (PHCC, n = 33 and IHCC, n = 14). Preoperative biliary drainage was applied in 32 of 33 cases with PHCC and 2 of 14 cases with IHCC. The mortality rate was 8.5% (n = 4). The complication rate was 68.1%. The R0 resection rate was 73% in PHCC. The mean OS time of PHCC cases that underwent R0 resection was 26.5 ± 24.8 months. The mean OS time of patients who underwent resection for IHCC was 28.7 ± 35.5 months. The OS was poorly affected by high CA19-9 levels (≥37 U/mL) (P = .005), the presence of lymphovascular invasion (P = .049), positive surgical margins after resection (P < .001), and the development of postoperative acute renal failure (P = .078). The OS of patients receiving adjuvant chemotherapy was significantly longer (P = .071). CA19-9 levels of more than 37 U/mL (P = .027) and positive surgical margin (P < .001) were independent factors for poor OS. Conclusion: Surgical resection is the mainstay of multidisciplinary treatment for PHCC and IHCC. In advanced stages of IHCC, the combination of loco-regional therapies and repeat surgery, along with the enhanced efficacy of systemic chemotherapy, plays a significant role in a patient’s survival. Cite this article as: Gundogdu A, Anil Kodalak T, Kucukaslan H, et al. Multidisciplinary approach to perihilar and intrahepatic cholangiocarcinoma: A single-center experience. Turk J Gastroenterol. 2025;36(1):34-44.